Names of birds in the Andean Spanish of Chota: An Ethnolinguistic Approach - Burga Muñoz, Wilmer (2021)
This research study the denominations of the names of the birds of the Andean Spanish in Chota from an ethnolinguistic approach. In this sense, it seeks to demonstrate the native languages and the linguistic processes present in the formation of names in these denominations. Likewise, the symbolic representation that these birds have in the world view of the Chota speakers is evidenced.